Comparison of WaveOne and ProTaper Universal Preparation Systems in the Amount of Smear Layer/Debris Production: an in-vitro SEM Study - N Roghanizad; M Vatanpour; L Moradi Eslami; H Bahrami (Islamic Azad University, 2017)
Background and Aim: Debris and the smear layer that remain after root canal preparations may result in failure of root canal therapies. The aim of this study was to compare the smear layer formation and the amount of residual debris following the use of WaveOne and ProTaper rotary files in mesiobuccal root canals of upper first molars by scanning electron microscopy (SEM). Materials and Methods: In this experimental study, 34 mesiobuccal root canals of human maxillary first molars with 20°-40° curvatures (according to Schneider technique) were randomly distributed in two experimental groups (15 each) and two control groups. The canals in test groups were instrumented according to the manufacturers' instructions. Five ml of 5.25% sodium hypochlorite (NaOCl) and 5 ml of normal saline were used as irrigants. The roots were split longitudinally, and apical, middle, and coronal radicular sections were randomly scanned by an SEM at ×1000 magnification. Two endodontists scored the data according to Schäfer and Schlingemann scoring system. Data of the amount of debris and smear layer were separately analyzed by Kruskal-Wallis test. Results: Although there was a slight difference in mean scores between the two groups (3.28 for WaveOne and 3.6 for ProTaper), no significant differences in debris amount were noted. The overall mean smear layer formation was not significantly different between the two groups (4.11 for WaveOne and 3.95 for ProTaper). Conclusion: There was no significant difference in remaining debris and smear layer in coronal, middle, and apical parts of root canals. However, ProTaper system appeared to produce less debris during preparation.